La desintegración familiar y su incidencia en el rendimiento escolar en los niños y niñas de 5to, 6to y 7mo grado de educación general básica de la escuela Cotopaxi del barrio Cangochara, cantón Espíndola, provincia de Loja, periodo 2013-2014 - Gaona Gaona, Nely Esperanza (2014)
Presently work of denominated thesis. THE FAMILY DISINTEGRATION AND THEIR INCIDENCE IN THE SCHOOL YIELD IN THE CHILDREN AND GIRLS OF 5to, 6to and 7mo GRADE OF BASIC GENERAL EDUCATION OF THE SCHOOL COTOPAXI OF THE NEIGHBORHOOD CANGOCHARA, CANTON ESPÍNDOLA, COUNTY DE LOJA, PERIOD 2013-2014. He/she thought about as general objective: To know how it affects of the family disintegration in the school yield of the children and girls of 5to, 6to and 7mo grade of Basic General Education of the School Cotopaxi of the Neighborhood Cangochara, Canton Espíndola, county of Loja, period 2013-2014. The investigation was developed with a sample of 40 students of 5to, 6to and 7mo grade of Basic General Education, 3 educational and 40 family parents. For the development of the investigative work it was necessary the use of the methods scientist, analytic - synthetic, inductive - deductive, being constituted in a systematic guide of the investigative process. The technique of the direct observation, the survey and the questionnaire like instrument, they made possible the gathering of the information toasted by the corresponding universe. You ended up concluding: Among the causes that cause the family disintegration in this educational establishment we have the migration, and the infidelity. The consequences of the family disintegration are the lack of support this way it affects in the school yield obtaining low qualifications. It would be necessary that the educational establishments have education department, to be able to help the children in the event of not being possible, the educational one should give chats to the children and the family parents on the disintegration, their causes and norms of coexistence. To urge the family parents and the students' other relatives so that they dedicate bigger time to their children, so that these feel that there is interest toward them and a desire of maintaining to the integrated family and in perfect harmony.